Attribution of the Climate and Land Use Change Impact on the Hydrological Processes of Athabasca River Basin, Canada - Sharad Aryal; Mukand S. Babel; Anil Gupta; Babak Farjad; Dibesh Khadka; Quazi K. Hassan (Hydrology)
Climate change (CC) and land use/land cover change (LULCC) are significant drivers of hydrological change, and an effective watershed management requires a detailed understanding of their individual and the combined impact. This study focused on the Athabasca River Basin (ARB), Canada, and investigated how the basin responded to their changes using the MIKE SHE-MIKE Hydro River. Our findings revealed novel insights into ARB hydrological changes, including increment in non-vegetated lands (0.26%), savannas (1.28%), forests (0.53%), and urban areas (0.02%) while grasslands (2.07%) and shrublands (0.03%) decreased. Moreover, the basin experienced rising annual minimum (1.01 °C) and maximum (0.85 °C) temperatures but declining precipitation (6.2%). The findings suggested a significant impact of CC compared to LULCC as CC caused annual reduction in streamflow (7.9%), evapotranspiration (4.8%), and recharge (6.9%). Meanwhile, LULCC reduced streamflow (0.2%) and recharge (0.4%) but increased evapotranspiration (0.1%). The study revealed spatiotemporal variability across the ARB, with temperature impacts stronger in winter and precipitation influencing other seasons.